Investigation of Epidemiological, Anatomical, and Risk Factors of the Thoracic Aortic Aneurysm and Dissection, in Mazandaran Heart Center - Zahedi, Mohammad; Alizade Navaie, Reza; Hoseini, Seyede Fateme; Mortazavi, Parham; Malekan, Mohammad; Allahverdi, Armin; Hooshmand, Shaghayegh; Azizi, Soheil (Archives of Men's Health, 2020)
Abstract Background: Aortic aneurysm is one of the most common cardiovascular diseases that can lead to numerous challenges for patients. The mortality rate of ruptured Thoracic Aortic Aneurysm (TAA) is observed to be high. In order to reduce this high rate, appropriate methods to diagnose TAA as well as its useful and aggravating factors are to be developed and/or identified. The objective of this study is the evaluation of the thoracic aortic aneurysm and dissection, in Mazandaran Heart Center. Method: This cross-sectional study with a census design was performed on all patients with thoracic aortic aneurysm and dissection who have undergone aneurysm surgery, from December 2010 to January 2019. Patients’ information was extracted from their medical records archive. SPSS 16.0 was used for statistical analysis. Result: From 53 patients with a thoracic aortic aneurysm, 77.4% were male. The mean age of patients was 59.70±12.07 years. 21 (39.6%) patients were more than or equal to 60 years old, while the remaining 32 (60.4%) were less than 60 years of age. The overall mortality rate was 11.3%. The mean aortic diameter of the patients was 5.42 cm. All patients had type A dissection. In other words, type B was not seen. Conclusion: Given the high prevalence and high mortality rate of thoracic aortic aneurysm, early screening can be beneficial and can increase the survival rate of patients. Laboratory and pathologic findings, along with clinical findings, can be very beneficial in early diagnosis. Keywords: Aneurysm aorta; thoracic aortic aneurysm; aneurysm dissection; risk factor